1987
DOI: 10.1007/bf01297582
|View full text |Cite
|
Sign up to set email alerts
|

Some nuclear and atomic properties of201Hg determined by conversion electron spectroscopy

Abstract: Conversion electron measurements with an electrostatic spectrometer proved the existence of the 1,565 __ 6 eV transition in 2~The conversion intensity ratios, N1/N2 = 1.2+0.2, NI/N3 = 1.1 +0.2, N2/N3 =0.92_+0.15, N4/N3=0.03+O.02 and Ns/N3 =0.04 _+ 0.02 were determined. These values agree with our calculations for the M 1 + E2 multipolarity with the E 2/M 1 mixing ratio 62= (1.1 _+ 0.3) x 10-4 and exclude all pure multipolarities with L__<4. The total conversion coefficient for the above M1 +E2 mixture was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The β-ray spectra were measured with the double-pass cylindrical mirror analyser [16] adjusted for the relative resolution E/E = 0.011 and transmission of 0.6% of 4π. The response function of the instrument was proved to be a Gaussian [22,23]. Magnetic shielding around the analyser cylinders reduces the earth magnetic field to about 30 nT.…”
Section: Electron Spectrometermentioning
confidence: 96%
“…The β-ray spectra were measured with the double-pass cylindrical mirror analyser [16] adjusted for the relative resolution E/E = 0.011 and transmission of 0.6% of 4π. The response function of the instrument was proved to be a Gaussian [22,23]. Magnetic shielding around the analyser cylinders reduces the earth magnetic field to about 30 nT.…”
Section: Electron Spectrometermentioning
confidence: 96%
“…(2.2). The resulting energy and angular distribution of the electrons is calculated by means of a Monte-Carlo simulation [24][25][26]. In the simulation the random values for starting depth of the electron in the substrate follow the distribution of 83 Rb atoms, which is calculated by means of the SRIM (Stopping and Range of Ions in Matter) code [27] for the known implantation energy of the atoms.…”
Section: Inelastic Part Of the Spectrummentioning
confidence: 99%
“…Several authors [11][12][13] proposed to excite, in a laser heated plasma, the first excited state of 201 Hg lying at 1564.8±1.0 eV. The existence of this level was first established by Dragoun et al [14] through the observation of the conversion electron spectrum following its decay. Later, Gerasimov et al [15,16] confirmed this result by observing the lines associated with the outer O subshells.…”
mentioning
confidence: 99%
“…The surface currents of the transition inside the nucleus and holes in the shell from which the electron is converted are taken into account. Table II displays the relative intensities of the partial conversion coefficients compared to the experimental ones [14][15][16]. Using both the mixing ratio values of (2.10 ± 0.55)10 −4 [15] and (1.1 ± 0.3)10 −4 [14], we obtain a total conversion coefficient of (6.50 ± 1.25)10 4 and (4.23 ± 0.68)10 4 , respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation